2008
DOI: 10.1080/14789940701877669
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life of violent and sexual offenders in community-based forensic psychiatric treatment

Abstract: Subjective well-being is a common outcome measure in the evaluation of treatment in general psychiatry, but not yet in forensic psychiatry. The impact of quality of life, defined in terms of objective indicators and subjective well-being, on criminal recidivism is unknown. Several criminological theories, such as Ward's good lives model, point at a possible relationship. In a study of male forensic psychiatric outpatients suffering from personality disorders, the quality of life of sexual and violent offenders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
9
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 37 publications
5
9
0
2
Order By: Relevance
“…Our results also show that the perceived health and quality of life of older male prisoners were significantly worse than those of the comparison men on all the sub‐scales of the Nottingham Health Profile and the WHOQOL. This is in line with other studies comparing prisoners with the general population (Chung et al, ; Blanc et al, ; Bouman et al, ; Cavallo et al, ). It is important to take prisoners' subjective evaluation into account, as the perception of poor health could be a major symptom of marginalisation in prison (Fraser et al, ).…”
Section: Discussionsupporting
confidence: 92%
“…Our results also show that the perceived health and quality of life of older male prisoners were significantly worse than those of the comparison men on all the sub‐scales of the Nottingham Health Profile and the WHOQOL. This is in line with other studies comparing prisoners with the general population (Chung et al, ; Blanc et al, ; Bouman et al, ; Cavallo et al, ). It is important to take prisoners' subjective evaluation into account, as the perception of poor health could be a major symptom of marginalisation in prison (Fraser et al, ).…”
Section: Discussionsupporting
confidence: 92%
“…Our results also show that the perceived health and quality of life of older male prisoners were significantly worse than those of the comparison men on all the sub-scales of the Nottingham Health Profile and the WHOQOL. This is in line with other studies comparing prisoners with the general population (Chung et al, 1998;Blanc et al, 2001;Bouman et al, 2008;Cavallo et al, 2014). It is important to take prisonersˈ subjective evaluation into account, as the perception of poor health could be a major symptom of marginalisation in prison (Fraser et al, 2009).…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with a study by Bouman, de Ruiter, and Schene ( 2008 ), no relation was found between social relations and overall QoL. This might suggest that forensic patients differ from other populations regarding this aspect.…”
Section: Discussionsupporting
confidence: 89%